Synthesis of single-phase high-entropy carbide powders. (15th March 2019) - Feng, Lun; Fahrenholtz, William G.; Hilmas, Gregory E.; Zhou, Yue
Abstract: High-entropy carbide powders were produced by a two-step synthesis process consisting of carbothermal reduction followed by solid solution formation. Nominally pure (Hf, Zr, Ti, Ta, Nb)C in a single-phase rock salt structure had an average particle size of about 550 nm and an oxygen content of 0.2 wt%. The fine particle size was due to the use of high-energy ball milling prior to carbothermal reduction combined with the relatively low synthesis temperature of 1600 °C. Oxygen content was minimized by completion of the carbothermal reduction reactions under vacuum. This is the first report of synthesizing a high-entropy carbide powder using individual transition metal oxides and carbon as precursors. Graphical abstract: Unlabelled Image